(untitled) - Griffin, Judith Berry (New York, 2002)
During the Revolution, Phoebe Fraunces has a chance to save the life of General George Washington while he has dinner at Mortier House in New York City.
Keywords: Spies,African American girls,Gián điệp; Biography,Biography,Tiểu sử; United States,New York (State),Hoa Kỳ